(untitled) (Fiep Bulletin - online, 2011)
Every human activity is motivated by some reason, the human being needs "pulse" to accomplish the several daily activities, and that motivation will also influence in the sports practice. The purpose of the present study was to investigate the children’s and adolescents’ motivational factors of children for swimming, taking into consideration the age and the gender. For the accomplishment of this study 77 swimming practicing people participated in the research aged from 08 to 14 year-old, the sample was no-probabilistic for convenience, the used instrument was the Scale of Reasons for Sport Practicing - EMPE (BARROSO; KREBS 2007), Brazilian validation of the instrument Participation Motivation Questionnaire (PMQ) (GILL; GROSS; HUDDLESTONE, 1983). The results presented that the most important reason for the practice of swimming is health, in which was detected that 57% of the sample consider the health as totally important. In relation to age, it can be verified that the reasons Context and the Affiliation are significantly more important for the smaller age children than for the larger age ones, what suggests the parents’, schools’ and family’s influence in the youngest children’s choice for the sports practice. Another data concerns the importance given to each reason for the attendance to the practice of swimming, it was observed that only for physical conditions had a statistic difference (p=0,01) among girls and boys, in which was possible to verify that for boys this is a significantly more important reason than for girls. This study allowed concluding that the reason for the choice of swimming is associated to the influence of significant people. Besides, it is possible to confirm the different meaning of the body for the boys, showing how much the body has a meaning related to the manliness and the virility, because the importance which is given to the body by the boys was significantly higher when compared to the girls.